Monte Carlo simulation of the LIDAL-ALTEA detector system. (May 2019) - Berucci, C; De Donato, C; Di Fino, L; La Tessa, C; Masciantonio, G; Messi, R; Morone, M C; Rizzo, A; Rovituso, M; Tommasino, F; Narici, L
Abstract: The LIDAL (Light Ion Detector for ALTEA) is a device designed to work paired with three silicon detector units of ALTEA (Anomalous Long Term Effects on Astronauts) in order to improve the particle identification capabilities of ALTEA on the International Space Station also providing Time-of-Flight measurements. The LIDAL-ALTEA goal is to measure ions from protons up to iron in real time. The improved measurements of the radiation environment inside ISS will be very valuable for radiation risk assessment and mitigation. It is necessary to have a detailed simulation of the apparatus response to cosmic ray nuclei in order to assess the detector response, its observational capabilities and to set the relevant parameters of the device. Here a new Monte Carlo simulation of the LIDAL-ALTEA setup and physics processes, in the framework of FLUKA, is presented. A comparison between Monte Carlo simulations and calibration data is also shown.